Insularity and Urban Hierarchies: the Case of La Reunion - Michel Dimou (European Regional Science Association (ERSA), 2006)
Modern urban landscapes are characterized by the progressive separation of the location of jobs, houses and amenities, which inexorably leads to the increase of urban travel and transit. This is the beginning point for some recent research programs in regional economics (Krugman, 1991 ; Glaeser, 1992 ; Henderson, 1997 ; Gabaix, 1999 ; Dobkins et Ioannides, 2000) which adopt a new line of reasoning based on the study of the commuting trips that characterise contemporary urban life. Different aspects of these trips, such as the volume, the pathways and the travel modes of the commuters, are examined with regard to mass transport, local public services and the increasing diversification of rural and urban amenities. This allows one to explore some original aspects of the recent transformations in both modern cities organisation and regional urban hierarchies and, by the way, identify institutional and policy responses to new urban problems such as traffic congestion or residential segregation (Brueckner, Thisse and Zenou, 2002 ; Mauer and Ott, 1999). However, instead of trying to define a general households' residential model, it seems then more appropriate to investigate the relationship between a given urban organisation and its regional macro-economic environment (Gabaix, 1999 ; Axtell and Florida, 2000). This point of view defend the hypothesis of a principle of structural dependence involving the action of long-term macroeconomic effects on the puzzling geometry of an urban economy (Marsili and Zhang, 1998 ; Simpson, 2000). By studying the case of La Reunion, this paper aims to study how insularity affects the locational choices of firms and households and their impact on regional urban hierarchies.
Keywords: 330